FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF PADA IBU PEKERJA - Sri Melda Br Bangun; Putri Damayanti Damanik; Basyariah Lubis (JURNAL KESMAS DAN GIZI (JKG), 2020)
Exclusive breastfeeding is breastfeeding for the first 6 months without drinks or eat other food additives. The low exclusive breastfeeding is a reason for the high infant mortality rate in Indonesia. The research aims to know the factors that effect of giving exclusive breastfeeding toward working mothers at Grandmed Hospital Lubuk Pakam such as the supporting of husband, breastfeeding place facilities, and the additional rest time. This research included an analytic observational quantitative study with a cross sectional design. The population is 21 person of working mothers. Data collection techniques are used questionnaires. The statistical test used in this research is chi-square and simple linear regression. The theoretical basis is the Green and Kreutzer Behavior Theory (1980). Based on the results and analysis of research, it was found that the majority of respondents aged are 26-30, with last education is D3, and they had babies aged 1-2 months. A total of 66.7% provide exclusive breastfeeding. There is a relationship of supporting husband with the giving of exclusive breastfeeding. The most dominant factor influenced giving of exclusive breastfeeding is husband's support factor where p-value=0,012<Î±(0.05). It is suggest for management of Grandmed Hospital to provide facilities that support Breastfeeding Corner like a icebox in the workplace and provide the opportunity to express milk during working hours